2014
DOI: 10.1111/hae.12421
|View full text |Cite
|
Sign up to set email alerts
|

Lack of recombinant factor VIII B‐domain induces phospholipid vesicle aggregation: implications for the immunogenicity of factor VIII

Abstract: Summary Factor VIII (FVIII) is a multi-domain blood plasma glycoprotein. Activated FVIII acts as a co-factor to the serine protease Factor IXa within the membrane-bound tenase complex assembled on the activated platelet surface. Defect or deficiency in FVIII causes hemophilia A, a severe hereditary bleeding disorder. Intravenous administration of plasma derived FVIII or recombinant FVIII concentrates restores normal coagulation in hemophilia A patients and is used as an effective therapy. In this work we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 40 publications
(40 reference statements)
2
25
1
Order By: Relevance
“…Both products are B‐domain‐modified; however, as moroctocog alfa (the third B‐domain‐modified product tested) had the highest number of subvisible particles, no correlation between the B‐domain structure of the rFVIII and the amount of subvisible particles present was observed in this study. Our findings are in contrast to previous studies on a more limited number of B‐domain‐modified products marketed at the time of the analyses, in which only one each of full‐length/BDD or two each of the full‐length/BDD rFVIII products were analysed, respectively. The SE‐HPLC method used in our study was not developed with the aim of quantifying the concentration of HMWP species in full‐length products; however, UV‐SE‐HPLC data suggest that moroctocog alfa contained a higher concentration of protein aggregates that elute very early compared with turoctocog alfa, simoctocog alfa, octocog alfa (modified BHK) and octocog alfa (CHO), which is in accordance with the relatively large SLS signal observed in the chromatogram at retention time around 17 minutes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Both products are B‐domain‐modified; however, as moroctocog alfa (the third B‐domain‐modified product tested) had the highest number of subvisible particles, no correlation between the B‐domain structure of the rFVIII and the amount of subvisible particles present was observed in this study. Our findings are in contrast to previous studies on a more limited number of B‐domain‐modified products marketed at the time of the analyses, in which only one each of full‐length/BDD or two each of the full‐length/BDD rFVIII products were analysed, respectively. The SE‐HPLC method used in our study was not developed with the aim of quantifying the concentration of HMWP species in full‐length products; however, UV‐SE‐HPLC data suggest that moroctocog alfa contained a higher concentration of protein aggregates that elute very early compared with turoctocog alfa, simoctocog alfa, octocog alfa (modified BHK) and octocog alfa (CHO), which is in accordance with the relatively large SLS signal observed in the chromatogram at retention time around 17 minutes.…”
Section: Discussioncontrasting
confidence: 99%
“…The licensed rFVIII products are produced from either a full‐length gene, resulting in a heterogeneous mixture of heavy chains (HCs) with different lengths of the B‐domain attached; B‐domain deleted (BDD); or from a B‐domain‐truncated construct with 21 amino acids of the naturally occurring B‐domain attached . Previous studies reported differences between the quality of the full‐length and B‐domain‐modified rFVIII preparations, that is in relation to the presence of aggregates and subvisible particles . Limited information is available on the contribution of different aggregates or aggregate characteristics in antibody‐mediated adverse events .…”
Section: Introductionmentioning
confidence: 99%
“…To gain more information on the conformational space of the FVIII membrane‐bound molecules at close to phsyiological conditions, we have helically organized two recombinant FVIII forms, human and porcine on PS containing LNT and collected cryo‐EM data as previously described . pFVIII is highly homologous to the human FVIII (86% sequence identity) . Both proteins are clinically used for the treatment of hemophilia A, as 30% of hemophilia A patients develop inhibitory antibodies against human FVIII and pFVIII is an effective replacement .…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins are clinically used for the treatment of hemophilia A, as 30% of hemophilia A patients develop inhibitory antibodies against human FVIII and pFVIII is an effective replacement . Both recombinant FVIII forms, lack the B domain, which makes them more homogenous and stable in solution than the plasma derived FVIII and activated FVIII (FVIIIa), thus more amenable for structural studies . We have optimized the helical organization of both proteins for high protein to lipid ratio (2:1, w/w) and PS to GC content (PS:GC = 4:1, w/w; Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human FVIII lacking the B domain (hFVIII) shows much less structural heterogeneity than pdFVIII and is more suitable for biochemical, biophysical and structural studies28. Porcine FVIII lacking the B domain (pFVIII) shares 86% amino acid sequence identity with hFVIII and has similar coagulation activity, forming functional FVIIIa-FIXa complexes with human FIXa in vivo 2829.…”
mentioning
confidence: 99%